2018
DOI: 10.1177/0022427818771109
|View full text |Cite
|
Sign up to set email alerts
|

Using Multitrait-Multimethod (MTMM) Techniques to Examine the Convergent and Discriminant Validity of Social Disorder

Abstract: Objectives: Disorder has been measured by various data sources; however, little attention has been given to comparing the construct validity of different measures obtained through various methods in capturing social disorder and related phenomena. Methods: The multitrait-multimethod approach was used to triangulate the consistency between social disorder, prostitution and drug activity across resident surveys, systematic social observations, and police calls for service data. Results: Prostitution and drug act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…However, some studies found weaker correlations, varying between r ¼ .32 (Conley et al, 2014) and r ¼ .10 (Drakulich, 2013). Yang et al (2018) did not find a significant association between observed and perceived social disorder. In no study, the proportion of covariance between perceived and observed disorder exceeded 50%, leaving ample room for other influences that have increasingly found scholarly interest and led to a change of perspective toward the subjective dimensions of urban disorder.…”
Section: The Discrepancy Between Survey-and Observation-based Measurementioning
confidence: 82%
“…However, some studies found weaker correlations, varying between r ¼ .32 (Conley et al, 2014) and r ¼ .10 (Drakulich, 2013). Yang et al (2018) did not find a significant association between observed and perceived social disorder. In no study, the proportion of covariance between perceived and observed disorder exceeded 50%, leaving ample room for other influences that have increasingly found scholarly interest and led to a change of perspective toward the subjective dimensions of urban disorder.…”
Section: The Discrepancy Between Survey-and Observation-based Measurementioning
confidence: 82%
“…The final way we expand our understanding of the validity of these measures is by constructing an MTMM matrix (Campbell & Fiske, 1959). Although there are some exceptions (e.g., Decker & Pyrooz, 2010; Rosenfeld & Decker, 1999; Van Voorhis, 1994; Yang et al, 2018), such tests are rare in criminology generally and in institutional corrections specifically. A core requirement for the matrix is that we obtain multiple measures (i.e., traits) from multiple data sources (i.e., methods).…”
Section: The Current Studymentioning
confidence: 99%
“…Finally, we construct a multitrait, multimethod (MTMM) matrix as a final indicator of methodological triangulation. MTMM has a long history in psychology, but is rare in criminology, offering an established test of validity (see Yang, Hinkle, & Wyckoff, 2018). Examining the overlap between primary data sources on prisoners is critically important to the advancement of theory and research in prisons, particularly the study of prison gangs, and has broad implications for measurement in criminology.…”
mentioning
confidence: 99%
“…We can deduce that the under-recording rates reported in the literature -and throughout this article -are exaggerated, but how much so is currently unclear. Measurement error estimation methods that do not rely on a gold standard, such as multitraitmultimethod latent variable models (Oberski et al, 2017;Yang et al, 2018) or hidden Markov models (Pavlopuolos et al, 2020), offer a particularly promising avenue of research. These can be used to estimate the validity and reliability of variables measuring the same concept, and, to the best of our knowledge, they…”
Section: Caveats and Future Avenues Of Researchmentioning
confidence: 99%